CONTRIBUTIONS OF THE PILOT PROJECT ON THE COLLECTION OF DATA ON RESEARCH IN THE AREA OF EDUCATION - Silva, Luis Henrique [UNESP]; Sampaio Oliveira, Anna Augusta [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2015)
In this article deal with the importance of the pilot project as a key resource for planning and analysis procedures that will be adopted in the construction of truly scientific sources through interviews. To this end, we present the entire trajectory of planning, implementation, analysis and restructuring of the interviews that we use as a resource for data collection in a dissertation whose focus was the analysis of the conception of success in teaching history for students with intellectual disabilities in a Regional Board of education of the State of Sao Paulo in Brazil. The results showed that the interview is in fact an important resource for gathering data on research involving the participation of students with intellectual disabilities, however, needs to be widely planned in order to reduce the chance of interference from several factors which, by their very nature, are capable of compromising the sample and therefore, the trustworthiness expected in academic papers.
Keywords: Interview; Feature; Pilot project